2018
DOI: 10.21831/pri.v1i2.22024
|View full text |Cite
|
Sign up to set email alerts
|

Happiness in early childhood

Abstract: This research was conducted based on three considerations. Firstly, childhood is a critical developmental stage that forms the foundation for the psychological well-being and future learning development of children. Secondly, the prevalence of child and adolescent behavioral problems is increasing, assumed to be caused by unhappiness. Thirdly, studies related to happiness in early childhood in Indonesia are still lacking. Therefore, this study aims to explore the meaning, situation, and parties associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
0
16
0
3
Order By: Relevance
“…Prior literature highlights the strong association between happiness and emotional competence, emphasizing on attaining greater emotional stability through happiness (Bajaj, Gupta, and Sengupta 2019;Chamorro-Premuzic, Bennett, and Furnham 2007;Hills and Argyle 2001; "NiramisaSutta: Unworldly" 2010). It is believed to be the state of psychological well-being of a child that promotes sharing habits and home learning influenced by various ways such as playbased learning, audio-visual aids, dancing, entertainment, reading comic books, sports, and drawing (Siegel 2007;Bajaj, Gupta, and Sengupta 2019;Singer 2013;Izzaty 2018). Thus, focusing on the happiness of children from early childhood is considered a crucial topic of research as a study has shown that happy children are likely to be more vigilant in recognizing and using their emotions in multifaceted social environments efficiently (Schultz et al 2004;United Nations Educational Scientific and Cultural Organization 2016).…”
Section: Conceptualizing Happinessmentioning
confidence: 99%
“…Prior literature highlights the strong association between happiness and emotional competence, emphasizing on attaining greater emotional stability through happiness (Bajaj, Gupta, and Sengupta 2019;Chamorro-Premuzic, Bennett, and Furnham 2007;Hills and Argyle 2001; "NiramisaSutta: Unworldly" 2010). It is believed to be the state of psychological well-being of a child that promotes sharing habits and home learning influenced by various ways such as playbased learning, audio-visual aids, dancing, entertainment, reading comic books, sports, and drawing (Siegel 2007;Bajaj, Gupta, and Sengupta 2019;Singer 2013;Izzaty 2018). Thus, focusing on the happiness of children from early childhood is considered a crucial topic of research as a study has shown that happy children are likely to be more vigilant in recognizing and using their emotions in multifaceted social environments efficiently (Schultz et al 2004;United Nations Educational Scientific and Cultural Organization 2016).…”
Section: Conceptualizing Happinessmentioning
confidence: 99%
“…Benefits of happiness for preschool children include the development of consistent behavior and optimism (Talebzadeh & Samkan, 2011). The studies by Holder (2012), Husted (2017), and Izzaty (2018) have shown a compelling association between school-related happiness and social relationships. These studies have accentuated happiness as one of the factors that influence the psychological well-being of children, which further affects their creativity, motor skills, social and emotional competence, and maturity (Holder, 2012;Husted, 2017;Izzaty, 2018).…”
Section: Benefits Of Happiness For Preschool Childrenmentioning
confidence: 99%
“…The concept of happiness, usually referred to as psychological well‐being or subjective well‐being, is among the factors that influence affecting a child's development (Izzaty, 2018). Most people, both today and in the past alike, express their desire for happiness and are in the pursuit of activities and materials that will help them achieve this aim.…”
Section: Introductionmentioning
confidence: 99%